2015
DOI: 10.1080/23737484.2015.1044050
|View full text |Cite
|
Sign up to set email alerts
|

On variance estimation for a Gini coefficient estimator obtained from complex survey data

Abstract: Obtaining variances for the plug-in estimator of the Gini coefficient for inequality has preoccupied researchers for decades with proposed analytic formulae often cumbersome to apply, in addition to being obtained assuming an iid structure. Bhattacharya (2007, Journal of Econometrics) provides an (asymptotic) variance when data arise from a complex survey, a sampling design common with data frequently used in inequality studies. Under a complex survey sampling design, we prove that Bhattacharya's variance esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…The most widely used measure of income inequality is the Gini coefficient (Hoque and Clarke 2015;Peñaloza 2016). Although these coefficients are typically calculated for individual or household incomes, we use them to examine the spatial patterns of inequality over time in the metropolitan area.…”
Section: Measures Of Inequalitymentioning
confidence: 99%
“…The most widely used measure of income inequality is the Gini coefficient (Hoque and Clarke 2015;Peñaloza 2016). Although these coefficients are typically calculated for individual or household incomes, we use them to examine the spatial patterns of inequality over time in the metropolitan area.…”
Section: Measures Of Inequalitymentioning
confidence: 99%
“…However, Hoque and Clarke (2015) showed that the estimators in (6) and (7) are numerically the same, i.e., V 2 n,1 = V 2 n,2 . We therefore chose V 2 n,1 as a consistent estimator of ξ 2 and drop the second subscript, without loss of generality (i.e., we use V 2 n as the estimator of ξ 2 ).…”
Section: Estimation Of ξmentioning
confidence: 99%
“…Wireless Communications and Mobile Computing Equation (3) offers a direct calculation method for Gini coefficient valued between 0 and 1, and the smaller, the more fair and the bigger the more unfair. Since this formula just involves the arithmetic operation of income data, this estimation method can be used unconditionally in theory without errors [22,23]. Based on the Lorenz curve and the calculation method, a simple formula was put forward by Jianhua [24] as follows:…”
Section: The Modelmentioning
confidence: 99%